P.050 Perspectives on the use of ancillary tests for determining neurological death: a survey of Canadian intensivists. (November 2021) - Neves Briard, J; Yu, M; Carvalho, LP; English, SW; d'Aragon, F; Lauzier, F; Turgeon, A; Dhanani, S; McIntyre, L; Shemie, SD; Knoll, G; Fergusson, DA; et al.
Abstract : Background: Ancillary tests are indicated to diagnose death by neurological criteria whenever clinical neurological examination is unreliable, but their use is variable and subject to debate. Methods: Survey of Canadian intensivists providing care for potential organ donors. We included closed-ended questions and different clinical scenarios regarding the use of ancillary tests. Results: Among 550 identified intensivists, 249 completed the survey. Respondents indicated they would be comfortable diagnosing death based on neurological examination without ancillary tests in the following scenarios: movement in response to stimulation (48%), spontaneous peripheral movement (31%), inability to evaluate upper/lower extremity responses (34%) or both oculocephalic and oculo-caloric reflexes (17%), presence of high cervical spinal cord injury (16%) and within 24 hours of hypoxemic-ischemic brain injury (15%). Furthermore, 93% agreed that ancillary tests should always be conducted when a complete neurological examination is impossible, 89% if there remains possibility of residual sedative effect and 59% in suspected isolated brainstem death. Conclusions: Our findings suggest that Canadian intensivists have different perceptions on what constitutes a complete and reliable clinical neurological examination for determining death by neurologic criteria. Some self-reported practices also diverge from national recommendations. Further investigation and education are required to align and standardize medical practice across physicians and systems.